Exploring the Physiological Link between Psoriasis and Mood Disorders - Cody J. Connor; Vincent Liu; Jess G. Fiedorowicz (Dermatology Research and Practice)
Psoriasis is a chronic, immune-mediated skin condition with a high rate of psychiatric comorbidity, which often goes unrecognized. Beyond the negative consequences of mood disorders like depression and anxiety on patient quality of life, evidence suggests that these conditions can worsen the severity of psoriatic disease. The mechanisms behind this relationship are not entirely understood, but inflammation seems to be a key feature linking psoriasis with mood disorders, and physiologic modulators of this inflammation, including the hypothalamic-pituitary-adrenal axis and sympathetic nervous system, demonstrate changes with psychopathology that may be contributory. Cyclical disruptions in the secretion of the sleep hormone, melatonin, are also observed in both depression and psoriasis, and with well-recognized anti-inflammatory and antioxidant activity, this aberration may represent a shared contributor to both conditions as well as common comorbidities like diabetes and cardiovascular disease. While understanding the complexities of the biological mechanisms at play will be key in optimizing the management of patients with comorbid psoriasis and depression/anxiety, one thing is certain: recognition of psychiatric comorbidity is an imperative first step in effectively treating these patients as a whole. Evidence that improvement in mood decreases psoriasis severity underscores how psychological awareness can be critical to clinicians in their practice.